Three-dimensional conductive graphene and carbon nano conductive agent capable of reducing internal resistance of lithium battery

By using conductive agents of three-dimensional conductive graphene, carbon nanotubes, composite carbon black and other components, a three-dimensional conductive network is constructed, which solves the shortcomings of existing conductive agents in improving the conductivity of lithium-ion battery electrodes, and has achieved significant reductions The effect of battery internal resistance.

CN119400862APending Publication Date: 2025-02-07CHAORONG NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411225469.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing lithium-ion battery conductive agents still have shortcomings in improving the conductivity of the electrodes and cannot meet the current application needs.

Method used

The conductive agent of three-dimensional conductive graphene, carbon nanotubes, composite carbon black and other components is used to construct a three-dimensional conductive network through specific proportions and treatment methods to improve the conductivity of the electrode.

Benefits of technology

By building a three-dimensional conductive network, the electronic transport resistance and charge transfer resistance are reduced, the internal resistance of lithium batteries is significantly reduced, and the performance of batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400862A_ABST
    Figure CN119400862A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional conductive graphene and carbon nano conductive agent capable of reducing the internal resistance of a lithium battery, the conductive agent in the scheme limits the components and proportions of graphene, carbon nano tubes, carbon black and the like, and when the conductive agent is applied to an electrode, the components are matched to well fill, connect and coat gaps and remote particles of active material particles, so that the internal resistance of the lithium battery is reduced. The constructed and formed three-dimensional conductive structure can provide an electron transfer channel for lithium ions in the embedding / dragging embedding process, fast movement of electrons is facilitated, meanwhile, fast movement of the lithium ions in electrolyte is facilitated, local electroneutrality is not damaged, electron transport resistance and charge transfer resistance are reduced, and therefore the purpose of reducing the internal resistance of the battery is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery devices, and in particular to three-dimensional conductive graphene and carbon nano conductive agents capable of reducing the internal resistance of lithium batteries. Background Art

[0002] Conductive agent is an important component of lithium-ion batteries. Although it accounts for a small proportion in the battery, it greatly affects the performance of lithium-ion batteries and plays a very important role in improving battery cycle performance, capacity utilization, rate performance, etc.

[0003] Conductive agents are also constantly evolving with the development of lithium-ion battery electrode materials. For example, from the earliest graphite and carbon black materials to today's carbon nanotubes, graphene and other conductive agents, the contact between electrode material particles has been continuously increased, greatly improving the conductivity of the electrode. However, it still cannot meet current application requirements and needs to be improved. Summary of the invention

[0004] To solve at least one of the above technical defects, the present invention provides the following technical solutions:

[0005] The present application document discloses three-dimensional conductive graphene and carbon nano conductive agent which can reduce the internal resistance of lithium battery, including 5-8% of graphene, 10-15% of carbon nanotubes, 15-25% of composite carbon black, 0.2-0.6% of anti-settling agent, 3-6% of dispersant and 45-70% of N-methylpyrrolidone. The composite carbon black includes SP conductive carbon black and KS-6 artificial graphite. The mass ratio of SP conductive carbon black and KS-6 artificial graphite is 2:0.8-1. The SP conductive carbon black is an agglomerate with a diameter of 150-200nm. The graphene is surface-modified by tryptophan.

[0006] In this scheme, the conductive agent is limited to components and proportions such as graphene, carbon nanotubes, and carbon black. When applied to the electrode, the components cooperate to fill, connect and coat the gaps between the active material particles and the remote particles well, and the constructed three-dimensional conductive structure can provide a channel for electron transfer during the embedding / drag-embedding process of lithium ions. Moreover, while the electrons move rapidly, it is beneficial for the lithium ions to move rapidly in the electrolyte without damaging the local electrical neutrality, thereby reducing the electron transport resistance and the charge transfer resistance, thereby achieving the purpose of reducing the internal resistance of the battery.

[0007] Tryptophan-modified graphene can help improve the dispersion and compatibility of graphene, reduce agglomeration, and thus improve its conductive properties.

[0008] Carbon black is a composite of SP conductive carbon black and KS-6 artificial graphite. SP conductive carbon black is in agglomerated state and dispersed in the middle of the active material to form a multi-branched conductive network, which can better reduce the physical internal resistance of the battery and improve electronic conductivity. KS-6 artificial graphite is filled in the middle of the active material to form an effective conductive path. The two play complementary and synergistic roles in lithium-ion batteries, and the combination of the two can further improve the conductive performance.

[0009] Further, graphene is added to a solvent and ultrasonically treated, then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added and stirred evenly, and the reaction is carried out for more than 20 minutes. L-tryptophan is added to a mixed solution of graphene and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and the reaction is carried out at room temperature for more than 20 hours. Then hydrazine hydrate is added and the temperature is increased to react for more than 4 hours, and the desired graphene is obtained by separation and drying.

[0010] In this scheme, graphene oxide is used as the raw material, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is used as the condensation agent. Tryptophan is grafted onto the graphene surface through an amidation reaction at room temperature, and then partially reduced with hydrazine hydrate. The modified graphene has better dispersibility, which helps to further improve the conductive performance.

[0011] Further, after adding hydrazine hydrate, the temperature is raised to above 70° C., centrifuged, washed and dried to obtain the desired graphene.

[0012] Furthermore, the conductive agent preparation process is as follows: carbon nanotubes, graphene, composite carbon black, anti-settling agent, dispersant, and N-methylpyrrolidone are mixed, and the mixed liquid is subjected to shear emulsification and high-pressure homogenization to obtain the desired conductive agent.

[0013] In this scheme, by continuously treating the mixed liquid through shear emulsification and high-pressure homogenization, part of the carbon black can be inserted between the graphene sheets, which can better improve the dispersibility in the slurry and help improve the conductive performance.

[0014] Furthermore, the shear emulsification rate is 4000-6000rpm, and the high-pressure homogenization pressure is 40-80MPa.

[0015] Furthermore, the particle size of KS-6 artificial graphite is 3-6 μm, and the flake size of the graphene is 1-15 μm. Limiting the particle size, flake size, etc. helps to improve performance.

[0016] Furthermore, the anti-settling agent is graphene aerogel, and the dispersant is one of polyvinyl alcohol and sodium dodecylbenzene sulfonate. Using graphene aerogel as the anti-settling agent helps prevent the sedimentation of graphene, improves dispersion stability, and improves the stability of the three-dimensional conductive network.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The conductive agent of the present invention is compounded with graphene, carbon nanotubes, carbon black and other components. When applied to the electrode, the components cooperate to construct a three-dimensional conductive network, which can provide a channel for electron transfer during the insertion / drag-insertion process of lithium ions, reduce the electron transport resistance and charge transfer resistance, and correspondingly reduce the internal resistance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 It is the microscopic morphology of graphene before and after modification. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0022] Treatment of graphene: Graphene oxide was added to solvent DMF at a mass volume ratio (mg / ml) of 2:1, and ultrasonically treated for 2 h. Then, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (30% of the mass of graphene oxide) was added, stirred evenly, and the reaction was stirred for 30 min.

[0023] L-tryptophan (accounting for 25% of the mass of graphene oxide) is added to a mixed solution of graphene and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and the mixture is reacted at room temperature for 26 hours. Then, hydrazine hydrate (accounting for 15% of the mass of graphene oxide) is added and the mixture is heated to 80°C for 6 hours. The product is centrifuged, washed and dried to obtain the desired graphene. Figure 1 As shown in the figure, the graphene agglomeration phenomenon is reduced after modification.

[0024] The particle size of KS-6 artificial graphite is 3-6μm.

[0025] The diameter of graphene sheets is 1-5 μm.

[0026] The carbon nanotubes are multi-walled, with an inner diameter of 2-5 nm, an outer diameter of 5-15 nm, and a length of 10-30 μm.

[0027] The anti-settling agent is graphene aerogel with a bulk density of 0.005-0.01g / cm 3 , porosity is 89-99%, specific surface area>1500m 2 / g.

[0028] The dispersant is sodium dodecylbenzene sulfonate.

[0029] Example 1

[0030] The preparation of three-dimensional conductive graphene and carbon nano conductive agent that can reduce the internal resistance of lithium batteries is as follows:

[0031] 1. Material preparation: by mass, the prepared graphene 6%, carbon nanotubes 12%, composite carbon black 18%, anti-settling agent 0.2%, dispersant 3%, N-methylpyrrolidone 60.8%, the composite carbon black includes SP conductive carbon black and KS-6 artificial graphite, the mass ratio of SP conductive carbon black and KS-6 artificial graphite is 2:1, and the SP conductive carbon black is an agglomerate with a diameter of 150-200 nm.

[0032] 2. Mix and stir carbon nanotubes, graphene, composite carbon black, anti-settling agent, dispersant and N-methylpyrrolidone, and then shear at 5500 rpm for 2 hours in a shear emulsifier, and then homogenize and disperse at 70 MPa for 45 minutes in a high-pressure homogenizer to obtain a conductive agent.

[0033] Example 2

[0034] The preparation of three-dimensional conductive graphene and carbon nano conductive agent that can reduce the internal resistance of lithium batteries is as follows:

[0035] 1. Material preparation: by mass, the prepared graphene is 7%, carbon nanotubes are 13%, composite carbon black is 20%, anti-settling agent is 0.4%, dispersant is 5%, and N-methylpyrrolidone is 54.6%. The composite carbon black includes SP conductive carbon black and KS-6 artificial graphite. The mass ratio of SP conductive carbon black and KS-6 artificial graphite is 2:0.8. SP conductive carbon black is an agglomerate with a diameter of 150-200 nm.

[0036] 2. Mix and stir carbon nanotubes, graphene, composite carbon black, anti-settling agent, dispersant and N-methylpyrrolidone, and then shear at 6000 rpm for 1.5 hours in a shear emulsifier, and then homogenize and disperse at 65 MPa for 40 minutes in a high-pressure homogenizer to obtain a conductive agent.

[0037] Example 3

[0038] The preparation of three-dimensional conductive graphene and carbon nano conductive agent that can reduce the internal resistance of lithium batteries is as follows:

[0039] 2. Material preparation: by mass, the prepared graphene is 8%, carbon nanotubes are 15%, composite carbon black is 22%, anti-settling agent is 0.6%, dispersant is 5%, and N-methylpyrrolidone is 49.4%. The composite carbon black includes SP conductive carbon black and KS-6 artificial graphite. The mass ratio of SP conductive carbon black and KS-6 artificial graphite is 2:1. SP conductive carbon black is agglomerates with a diameter of 150-200 nm.

[0040] The carbon nanotubes, graphene, composite carbon black, anti-settling agent, dispersant and N-methylpyrrolidone were mixed and stirred evenly, then sheared at a speed of 4500 rpm for 2.5 hours in a shear emulsifier, and then homogenized and dispersed at 80 MPa for 30 minutes in a high-pressure homogenizer to obtain a conductive agent.

[0041] Comparative Example 1

[0042] The preparation of the three-dimensional conductive graphene and carbon nano-conductive agent which can reduce the internal resistance of the lithium battery in this example is different from that in Example 1, except that the composite carbon black is replaced by the same weight of KS-6 artificial graphite.

[0043] Comparative Example 2

[0044] The preparation of the three-dimensional conductive graphene and carbon nano-conductive agent which can reduce the internal resistance of the lithium battery in this example is different from that in Example 1, except that the graphene is not modified with tryptophan.

[0045] The performance of the conductive agent prepared above was tested. The ternary NCM523, LMO, PVDF, and conductive agent were mixed in a mass ratio of 50:44:3:6, and then an appropriate amount of N-methylpyrrolidone was added to prepare a slurry with a viscosity of 10000 mPa.S. A lithium-ion battery was made with the conductive slurry, and the battery internal resistance test was performed, as shown in Table 1.

[0046] Table 1

[0047] Battery internal resistance (mΩ) Example 1 24 Example 2 20 Example 3 23 Comparative Example 1 35 Comparative Example 2 40

[0048] It can be seen that the internal resistance of the battery is significantly reduced and the battery performance is further improved. It can be considered that the three-dimensional conductive structure formed by the conductive agent limited graphene, carbon nanotubes, carbon black and other components has indeed reduced the electron transport resistance and charge transfer resistance, thereby achieving the purpose of reducing the internal resistance of the battery.

[0049] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A three-dimensional conductive graphene or carbon nano conductive agent capable of reducing the internal resistance of a lithium battery, characterized in that: The invention comprises 5-8% of graphene, 10-15% of carbon nanotubes, 15-25% of composite carbon black, 0.2-0.6% of an anti-settling agent, 3-6% of a dispersant and 45-70% of N-methylpyrrolidone. The composite carbon black comprises SP conductive carbon black and KS-6 artificial graphite. The mass ratio of the SP conductive carbon black to the KS-6 artificial graphite is 2:0.8-1. The SP conductive carbon black is an aggregate with a diameter of 150-200nm. The graphene is surface-modified by tryptophan.

2. The three-dimensional conductive graphene and carbon nano-conductive agent capable of reducing the internal resistance of lithium batteries as claimed in claim 1, characterized in that: Graphene is added to a solvent and subjected to ultrasonic treatment. Then, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added and stirred evenly. The reaction is carried out for more than 20 minutes. L-tryptophan is added to a mixed solution of graphene and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. The reaction is carried out at room temperature for more than 20 hours. Then, hydrazine hydrate is added and the temperature is raised to react for more than 4 hours. The desired graphene is obtained by separation and drying.

3. The three-dimensional conductive graphene and carbon nano-conductive agent capable of reducing the internal resistance of lithium batteries as claimed in claim 2, characterized in that: After adding hydrazine hydrate, the temperature is raised to above 70° C., and the desired graphene is obtained by centrifugation, washing and drying.

4. The three-dimensional conductive graphene and carbon nano-conductive agent capable of reducing the internal resistance of lithium batteries as claimed in claim 1, characterized in that: The preparation process of the conductive agent is as follows: carbon nanotubes, graphene, composite carbon black, anti-settling agent, dispersant, and N-methylpyrrolidone are mixed, and the mixed liquid is subjected to shear emulsification and high-pressure homogenization to obtain the desired conductive agent.

5. The three-dimensional conductive graphene and carbon nano-conductive agent capable of reducing the internal resistance of lithium batteries as claimed in claim 4, characterized in that: The shear emulsification rate is 4000-6000rpm, and the high-pressure homogenization pressure is 40-80MPa.

6. The three-dimensional conductive graphene and carbon nano-conductive agent capable of reducing the internal resistance of lithium batteries as claimed in claim 1, characterized in that: The particle size of KS-6 artificial graphite is 3-6 μm, and the sheet size of the graphene is 1-15 μm.

7. The three-dimensional conductive graphene and carbon nano-conductive agent capable of reducing the internal resistance of lithium batteries as claimed in claim 1, characterized in that: The anti-settling agent is graphene aerogel, and the dispersant is one of polyvinyl alcohol and sodium dodecylbenzene sulfonate.

Citation Information

Patent Citations

  • Composite conductive agent, lithium ion battery positive electrode and lithium ion battery

    CN108258245A

  • Conductive paste, preparation method and application thereof, and battery

    CN110620237A

  • Preparation method of graphene composite conductive paste for lithium battery

    CN113745516A

  • Lithium-manganese button cell positive electrode material doped with graphene, preparation method and application

    CN114695895A

  • Positive pole piece with three-dimensional conductive network structure and preparation method of positive pole piece

    CN115117297A

Cited By

  • Low-internal-resistance lithium ion battery construction method based on graphene-carbon nanotube three-dimensional conductive structure

    CN120261726A